2018
DOI: 10.1111/dth.12690
|View full text |Cite
|
Sign up to set email alerts
|

Topical urea in skincare: A review

Abstract: Alterations in barrier function are associated with a number of skin diseases, including xerosis, atopic dermatitis, and psoriasis. Urea, a component of the natural moisturizing factor of the skin, plays an important role in the preservation of skin hydration and integrity. Several studies have investigated the effects of urea in the clinical setting. Here, we summarize the available clinical evidence regarding the effects of urea in the maintenance of healthy skin and management of skin disorders. At lower do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
100
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 44 publications
0
100
0
9
Order By: Relevance
“…Urea has been safely used for over a century in the maintenance of healthy skin and the treatment of several skin conditions. Clinical studies have confirmed the positive effects of urea in several studies 33 . Urea‐containing topical formulations are available at different concentrations and provide clinicians with a wide array of alternatives to improve the management of skin.…”
Section: Discussionmentioning
confidence: 90%
“…Urea has been safely used for over a century in the maintenance of healthy skin and the treatment of several skin conditions. Clinical studies have confirmed the positive effects of urea in several studies 33 . Urea‐containing topical formulations are available at different concentrations and provide clinicians with a wide array of alternatives to improve the management of skin.…”
Section: Discussionmentioning
confidence: 90%
“…It has been proposed that improving hydration of the stratum corneum and diminishing inflammation using topical emollients could facilitate the prevention and mitigation of certain inflammation-associated chronic disorders such as psoriasis [21][22][23][24][41][42][43][44]. When used alone or as an adjunct, essential topical therapy can restore and protect skin barrier function, prolong the interval between psoriasis flare-ups, and enhance the effects of pharmaceutical therapy [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a skin irritation study has indicated that EtOH did not disrupt the skin barrier or exacerbate irritation even on irritated skin [19,20]. There is consensus that emollients and moisturizers containing humectants that hydrate the stratum corneum are a standard adjuvant therapy for managing inflammatory skin disorders such as psoriasis [21][22][23][24]. This study intends to determine the optimal carrier system for Sal.…”
Section: Introductionmentioning
confidence: 99%
“…From the excellent contributions of this issue some considerations can be made. Urea represents an old molecule 8‐9 still very useful in dermatology and not replaceable with other substances, because of its unique moisturising, keratolytic and antimicrobial properties that are exerted in a dose‐dependent manner 10 Urea‐based products are widely used and marketed worldwide, with costs generally affordable.…”
Section: Figurementioning
confidence: 99%
“…The safety of urea is supported by several studies and by long‐lasting use in clinical practice. No toxicity has been reported despite its widespread use, and the side effects (redness, stinging and burning sensation) are uncommon, slight, transient and generally related to higher strength concentrations 10,11,17 . Urea products are in general cosmetically well‐accepted by the patients, especially lotions and creams that are nongreasy and easily spreadable on large area of the body.…”
Section: Figurementioning
confidence: 99%